Estudio del perfil metabólico de los complejos ovocito-cumulus porcinos en la maduración in vitro - Alvarez, Gabriel Martín (2010)
The in vitro porcine embryo production technique needs to be improved. Inefficient oocyte in vitro maturation is one of the main causes of the embryo production failure. The cumulus-oocyte complex (COC) metabolism and its regulation by gonadotropins are relevant aspects that remain unclear. Although immature cumulus features are related to oocyte maturation ability, those features lack clearly defined evaluation criteria. In addition, the relation between cumulus characteristics and COC metabolic activity has not been considered. The main purpose of this work was to evaluate the metabolic profile of porcine COC during in vitro maturation. The specific aims were: to establish immature oocyte quality, to evaluate oocyte in vitro maturation in each COC class and to study the influence of cumulus and gonadotropins on carbohydrates, amino acids and lipid metabolism and reactive oxygen species (ROS) production during in vitro maturation. Immature COCs were allotted into six different classes (A1, A2, B1, B2, C and D) according to their size and morphological criteria. COCs able to complete nuclear maturation (A1, A2, B1 and B2) were matured with and without gonadotropins to evaluate cumulus and hormonal influence on metabolism. Variations of glucose, lactate and ammonia concentrations in maturation media, amounts of COC protein and oocyte neutral lipid and endogenous ROS levels were measured. In addition, the number of cumulus cells of each COC class and its variation due to the influence of gonadotropins during in vitro maturation were evaluated.\nAlthough a higher rate of live immature oocytes was observed in A classes, the percentages of oocytes at germinal vesicle stage were similar between A, B and C classes. The nuclear maturation rates after in vitro culture were the same in classes A and B, but cytoplasmic maturation was higher in class A1. The number of cumulus cell was the same in both A classes, raising with gonadotropic stimulation during maturation and decreasing during culture without hormones. The cumulus cell number\nobserved in B classes was lower and showed no variation during culture with or without gonadotropins. Glycolysis would be the main fate of glucose consumption showed by porcine COC during in vitro maturation, as suggested by the high positive correlation and molar rate 1:2 observed between glucose consumption and lactate production. Glycolysis and ammonia production were higher in A classes. Both pathways showed increased activity during gonadotropic stimulation and the hormonal effect was more intense in class A1 COCs. No association was found between the glycolytic activity and the nuclear maturation of oocytes when both aspects were evaluated simultaneously. Sodium fluoride (NaF) and ATP induced glycolysis and nuclear maturation inhibition. AMP showed no effect on glycolytic activity in the presence or absence of gonadotropins, but it diminished metaphase II rate. Protein content of immature COC was higher in A classes. After maturation without gonadotropins no modification was observed, but hormonal stimulation induced a similar raise in the amount of proteins present in both A classes. Equal neutral lipid content and ROS levels were observed in immature oocytes from classes A1, A2, B1 and B2. Both parameters showed the same decrease after maturation in the presence or absence of gonadotropins. In addition, culture media supplementation with cysteine induced a greater decrease in ROS levels in oocytes belonging to all evaluated classes.\nImmature oocyte vitality would be associated with cumulus features, but germinal vesicle stage seems to be the main factor affecting nuclear maturation. Oocytes from classes A and B could reach metaphase II stage regardless of cumulus characteristics. However cytoplasmic maturation would be closely associated to the surrounding cumulus. Glycolysis and amino acid metabolism mainly take place in cumulus cells. The higher protein content in immature class A COCs could be partly due to their greater cumulus cell number. The increase of glycolysis, amino acid catabolism and protein synthesis in response to gonadotropins would be partly mediated by the higher number of cumulus cells. However class A1 particularities would\nallow a greater metabolic response to hormones. Glycolysis in cumulus cells seems not to be associated with oocyte nuclear progress, but the activity of this pathway would be required for oocytes during in vitro maturation to reach metaphase II stage. Lipid content and ROS levels of immature oocytes would not be associated with cumulus features. The lipid consumption and the decrease in ROS levels during in vitro oocyte maturation seem to be independent of the surrounding cumulus and gonadotropic stimulation. Thus, oocyte metabolism itself would regulate those aspects without cumulus participation. Cysteine supplementation to culture medium would contribute to diminish ROS production in oocytes during in vitro maturation without cumulus influence. In conclusion, oocytes surrounded by a complete and dense cumulus would be more competent for in vitro maturation. Gonadotropic stimulation of carbohydrates and amino acid metabolism in cumulus cells would improve oocyte maturation. Oocyte lipolysis and ROS production would be independent of the surrounding cumulus and gonadotropic regulation.